eLEARNING APPROACH eBIG3 : DEVELOPMENT , DELIVERY , AND EVALUATION - Žuga, Bruno; Kapenieks, Kristaps; Vītoliņa, Ieva; Mangusa, Līga; Kapenieks, Atis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In this report in addition to previous results we present the evaluation results of multi-screen e-learning courses – eBig3. It is a new approach and technology to lifelong learning embodying effective integration of popular television, Internet, and mobile phones technologies. We present the results of ten eBig3 pilot courses delivered in 2013 in Latvia. The target group of eBig3 courses was society at large. It demonstrates radical increase of registration in eBig3 courses compared with the traditional registration in the Internet. The course delivery was more successful than that of blended learning courses. The new approach strongly increases the availability of e-courses, and contributes to closing the gap between the expectations for future life-long-learning and real achievements. We didn’t observe connection between learner’s age and attitude towards the usage of SMS in the eBig3 approach.